Magkalayong agwat, paano ba mag-adjust? the role of dyadic coping in relationship satisfaction among distal romantic relationships - Borja, Meyrick Kirby L.; Cordero, Krystelle A.; Samson, Azenette O.; Yu, Maera Trisha D. (2023)
In the Philippines, according to a Social Weather Survey (SWS) in 2015, 67% of Filipinos believe in long-distance relationships. The deprivations caused by the pandemic to proximal romantic relationships have also enabled Filipinos to shift to distal romantic relationships. According to Du Bois et al. (2016), people who are in love have greater amounts of stress hormones, and being apart from their partner is likely to amplify those effects. As such, couples would often cope with stressful situations together rather than individually--this is known as Dyadic Coping. This way of managing stress can often be seen in couples going through chronic diseases or illnesses such as cancer. With this, the present study aimed to discover how couples cope with stressful repercussions that come with being in a distal romantic relationship and how it affects their relationship satisfaction through the use of a medication analysis. Results have shown that dyadic coping is a significant predictor for relationship satisfaction. However, perceived stress has also been discovered to have minimal effect on dyadic coping as a predictor for relationship satisfaction and therefore cannot stand as a mediating variable. Furthermore, the present study has also revealed that couples who apply supportive and collaborative coping strategies together tend to have higher levels of relationship satisfaction. Therefore, couples' interventions and counseling programs should then be aimed at improving the aforementioned strategies to manage stress.